Aflatoxin B1-Induced Kidney Damage in Rats - Al-Habib, May Fadhil Majid; Jaffar, Akram Abood; Abdul-Ameer, Hayder Hammadi (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Aflatoxin B1 (AFB1) is a widely distributed mycotoxin in nature. Several investigations have shown its biological effects on different organs and in different animal species. However, the effects of AFB1 on the rat kidney have not been much elucidated histologically. Objective: This study aims to demonstrate the effects of AFB1 contaminated diet on the rat kidney from the histological and morphometric aspects. Method: Twelve mature albino rats were divided equally into a control group fed with usual diet and a treated group which was daily fed with diet contaminated with 20 mg AFB1/kg of body weight for 30 days. Semithin sections from renal cortex were stained with methylene blue and examined by light microscopy. Corpuscular changes were also detected morphometrically in terms of the ratio between the area of Bowman’s capsule and the area of its contained glomerulus (B/G ratio). Results: The treated group showed a marked increase in body weight. Histologically, there was evidence of acute tubular necrosis and increase in urinary space. Morphometrically, there was a diffuse significant increase in the B/G ratio compared to the control. Conclusion: Gain in weight can be attributed to fluid retention that accompanies the ensuing renal damage. The dietary dose of AFB1 (20 mg/kg of body weight) for 30 days was sufficient to produce acute tubular necrosis. The corpuscular changes indicated by the increase in the B/G ratio can be attributed to compensatory hypertrophy.